2019
DOI: 10.1007/s10006-019-00783-0
|View full text |Cite
|
Sign up to set email alerts
|

Dental intervention against osteoradionecrosis of the jaws in irradiated patients with head and neck malignancy: a single-arm prospective study

Abstract: Dental intervention against osteoradionecrosis of the jaws in irradiated patients with head and neck malignancy: a single-arm prospective study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…However, interestingly the phenomenon in the early years particularly affected the HPV-positive group. A closer analysis revealed this 'spontaneous' group was in actual fact 'induced pre-RT' following a radical dental approach of prophylactic extractions of teeth deemed to be a future concern, a concept 12,15,[42][43][44] well recognised (Table 5) and previously attributed to OPC. The pattern evident in the current study was that ORN in pre-RT dental extraction (12.9%, 29/224) was almost double compared to those not having pre-RT dental extractions (6.6%, 9/137).…”
Section: Discussionmentioning
confidence: 95%
“…However, interestingly the phenomenon in the early years particularly affected the HPV-positive group. A closer analysis revealed this 'spontaneous' group was in actual fact 'induced pre-RT' following a radical dental approach of prophylactic extractions of teeth deemed to be a future concern, a concept 12,15,[42][43][44] well recognised (Table 5) and previously attributed to OPC. The pattern evident in the current study was that ORN in pre-RT dental extraction (12.9%, 29/224) was almost double compared to those not having pre-RT dental extractions (6.6%, 9/137).…”
Section: Discussionmentioning
confidence: 95%
“…This trend follows the findings by Owosho et al 31 who reported an overall median of 19.1 months with the occurrence in OPC patients at 14.6 months, while in OCC patients this was 36.1 months once again highlighting both tumour sites to be at risk but with differing timeframes for ORN. This early phase of ORN in OPC has been highlighted by various authors due to pre‐RT dental extractions 11,12,42‐45 with the sites having limited time to heal and following which the area is impacted by chemo‐RT. This phenomenon is stark in the OPC patient due to their attendance with a more complex dentition including more teeth than most other HNC sub‐sites and the radical practice of prophylactic extraction 26,27,45,46 or aggressive dental care 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of the efficacy of elimination of oral foci of infection to prevent postradiotherapy oral sequelae is growing (Beech et al, 2014;Eliyas et al, 2013;Jansma et al, 1992;Muraki et al, 2019;Schuurhuis et al, 2011Schuurhuis et al, , 2018Sennhenn-Kirchner et al, 2009), and in particular what to consider as an oral focus of infection in specific patient groups. We suggest, based on the literature, that the following should be considered as an oral focus of infection in HNC patients:…”
Section: What To Consider As An Oral Focus Of Infection In Hnc Patimentioning
confidence: 99%
“…The evidence of the efficacy of elimination of oral foci of infection to prevent postradiotherapy oral sequelae is growing (Beech et al, 2014; Eliyas et al, 2013; Jansma et al, 1992; Muraki et al, 2019; Schuurhuis et al, 2011, 2018; Sennhenn‐Kirchner et al, 2009), and in particular what to consider as an oral focus of infection in specific patient groups. We suggest, based on the literature, that the following should be considered as an oral focus of infection in HNC patients: deep caries in which excavation may lead to pulpal exposure; active periodontal disease with pockets ≥ 6 mm, furcation > grade 1, mobility > grade 1, gingival recession ≥ 6 mm, and especially a combination of these periodontal problems; non‐restorable teeth with large restorations, especially those extending the gum line or with root caries; periapical granuloma and avital teeth; (partially) impacted or partially erupted teeth not fully covered by bone or showing radiolucency; cysts and other radiographic abnormalities. …”
Section: Head and Neck Cancermentioning
confidence: 99%
See 1 more Smart Citation